Training induced changes in maximum heart rate - Whyte, G. P.; George, K.; Shave, R.; Middleton, N.; Nevill, A. M. (International Journal of Sports Medicine, 2008)
The present study aimed to examine maximum heart rate (HRmax) in elite athletes. 130 (68 male, 23.2 ± 4.8 years, 62 female, 21.0 ± 5.1 years) endurance trained athletes, 40 (24 male, 24.0 ± 5.6 years, 16 female, 22.8 ± 4.6 years) anaerobically trained athletes, and 95 (39 male, 24.8 ± 4.8 years, 56 female, 23.0 ± 4.8 years) sedentary participants entered the study. All participants undertook a standard ramp protocol to volitional exhaustion to establish HRmax. Significant differences in HRmax were identified due to mode of exercise (p < 0.001) and gender (p = 0.001). The mean HRmax for the three modes of exercise were; aerobic 190.3 (SEE = 0.66), anaerobic 190.1 (SEE = 1.12) and sedentary 194.8 (SEE = 0.73) beats · min-1 estimated at the average age of 23.1 years. The slope parameter for age varied between genders, the beta slope for females being significantly more negative than male subjects (- 1.1 beats · min-1 · year-1 vs. - 0.55 beats · min-1 · year-1, respectively). The predictive HRmax equation for male athletes was HRmax = 202 - 0.55 × age, and for female athletes it was HRmax = 216 - 1.09 × age. HRmax is similar between aerobically and anaerobically trained athletes. HRmax is significantly lower in athletes compared with age matched sedentary counterparts. The mechanisms underlying the lower HRmax remain to be elucidated.